Influence of Adjuvant Radiotherapy Timing on Survival Outcomes in High-Risk Patients Receiving Neoadjuvant Treatments - Cao, Lu; Xu, Cheng; Wang, Meng-Di; Qi, Wei-Xiang; Cai, Gang; Cai, Rong; Wang, Shu-Bei; Ou, Dan; Li, Min; Shen, Kun-Wei; Chen, Jia-Yi (Frontiers in Oncology, 2022)
Purpose To determine the relationship between time to radiotherapy (TTR) and survival outcomes in breast cancer (BC) patients treated with neoadjuvant treatments (NATs). Methods Continuous non-metastatic BC patients receiving NAT and adjuvant radiotherapy (RT) from 2009 to 2016 were retrospectively reviewed. A multivariable Cox model with restricted cubic splines (RCSs) was used to determine the panoramic relationship between TTR and survival outcomes. Multivariable analysis was used to control for confounding factors between the groups of TTR. Results A total of 315 patients were included. The RCS modeling demonstrated a non-linear relationship between TTR and survival outcomes. The lowest risk for distant metastasis-free survival (DMFS) and recurrence-free survival (RFS) was observed at the TTR of 12 weeks, and the lowest risk of BC-specific survival (BCSS) at 10 weeks. TTR was accordingly transformed into categorical variables as ≤10, 11–20, and >20 weeks. Multivariable analysis revealed that the TTR of ≤10 weeks was an independent prognostic factor for worse DMFS (HR = 2.294, 95% CI 1.079–4.881) and RFS (HR = 2.126, 95% CI 1.038–4.356) compared with the TTR of 10–20 weeks, while the is no difference in DMFS, RFS, and BCSS between TTR >20 weeks and TTR of 10–20 weeks. Conclusion There exists a non-linear relationship between TTR after surgery and survival outcomes in patients treated with NAT. Early initiation of RT following surgery does not seem to be associated with a better therapeutic outcome. A relatively flexible recommendation of TTR could be adopted in clinical practice.